Wildlife corridor use amongst reticulated giraffes (Giraffa camelopardalis reticulata) at Ol Pejeta Conservancy, Kenya - Lund, Johanna (SLU/Dept. of Animal Environment and Health (until 231231), 2019)
The African continent is home to many large and unique wildlife species and is, as is commonly known, considered to be the birthplace of the human race. The numbers and strength of this wide array of species is however diminishing rapidly before our eyes (Campbell et al., 2003; Ogutu et al., 2016). In merely the last three decades, the population of reticulated giraffe (Giraffa camelopardalis reticulata) in Africa has seen a rapid decline of 56% with a steady downward trend (Muneza et al., 2018). The reticulated giraffe is since March 2018 listed as endangered on the International Union for Conservation of Nature’s (IUCN) red list of threatened species and there are currently an estimated 11,000 reticulated giraffe roaming the East African plains. This study aims to gain further knowledge about migration behaviour, specifically the use of wildlife corridors, in reticulated giraffes in order to better understand the needs of this magnificent species and thereby facilitate work in constituting strategies of conservation. The study took place at Ol Pejeta Conservancy, a 360 km2, fenced, private reserve in Laikipia County, Kenya. Camera traps set up at three specific entrance/exit points in the fence, recorded passages in and out of the conservancy for a total period of three years (October 2015–September 2018). The data collected for reticulated giraffes consisted of approximately 30,000 images, from which 563 passages were excerpted. For each passage time, date, choice of corridor (1–3), direction of travel, sex, group size and lunar phase were noted. If possible, individual giraffes were identified by their unique coat pattern. A passage was defined as a single animal passing through the wildlife corridor either in or out of the conservancy. Weather data consisting of temperature, precipitation and cloud coverage was obtained online. The different variables were analysed in order to find spatial and temporal factors correlating to giraffe migration. A total of 563 passages were recorded and in 461 of them the sex could be verified. Male giraffes accounted for 447 of these passages (97% of all passages with recorded sex) and females 14 (i.e., only 3% of all passages with known sex) during the three-year period. Passages were made significantly more often during early morning and late evening (p<0.005) with peak in-passages recorded in the morning and out-passages in the afternoon. Mean group size was 1.6 giraffes, where lone bulls accounted for 85% of all single animal passages (n=396). Corridor 2 was favourited by the giraffes, while the other two corridors were rarely used. During the night, giraffes were more inclined to use the corridors during high lunar luminosity and less so during low lunar luminosity. No impact of temperature or cloud coverage on giraffe migration was seen in this study; the impact of current previous precipitation remained unclear. The reasons for male giraffe migration in and out of the conservancy could not be determined within this study but is hypothesised to be a result of search for receptive females in oestrus and/or as a part of predator avoidance.